Dramatic response to pembrolizumab with chemotherapy followed by salvage surgery in a lung cancer patient. Issue 15 (21st June 2021) - Saito, Shunichi; Toyokawa, Gouji; Momosaki, Seiya; Kozuma, Yuka; Shoji, Fumihiro; Yamazaki, Koji; Takeo, Sadanori
Abstract: Immune checkpoint inhibitors with chemotherapy have been shown to exhibit remarkable efficacy for advanced non‐small‐cell lung carcinoma and are under investigation as an induction therapy. However, the significance of preoperative therapy with pembrolizumab + chemotherapy for surgically resectable non‐small‐cell lung carcinoma still remains unclear. Here, we report a case of stage IIIB non‐small‐cell lung carcinoma that underwent salvage surgery after three cycles of pembrolizumab + carboplatin + nab‐paclitaxel. Computed tomography revealed the remarkable decrease in tumor volume by 81%. A pathological examination showed that viable neoplastic cells were observed in <1% of the total tumorous lesion suggesting near pathological complete response. This case suggests that this regimen might be a good option as induction therapy for non‐small‐cell lung carcinoma. Abstract : Significance of preoperative therapy with pembrolizumab + chemotherapy for surgically resected non‐small‐cell lung carcinoma still remains unclear. This regimen showed a drastic response in a case of stage IIIB non‐small‐cell lung carcinoma that underwent salvage surgery after three cycles. A pathological examination showed that viable neoplastic cells were observed in <1% of the total tumorous lesion suggesting near pathological complete response.